Patient's classification according to complications and mortality risks after elective heart surgeries - Carina Aparecida Marosti Dessotte; Mariana Lopes Figueiredo; Hélen Francine Rodrigues; Rejane Kiyomi Furuya; Lidia Aparecida Rossi; Rosana Aparecida Spadoti Dantas (Universidade Federal de Goias, 2016)
The investigation objective was to classify patients according to the complication and mortality risks after elective heart surgeries, using the Tuman System of Clinical Risk Score. A descriptive study, developed in a university hospital in São Paulo state, Brazil, from August of 2013 to February of 2015. A consecutive and non-probabilistic sample was constituted by patients submitted to a first myocardial revascularization surgery and/or surgeries to correct valvulopathies, and with elective scheduling of their surgeries. Results: One-hundred and twenty five patients participated. The majority presented low risk for development of post-surgery complications and mortality (n = 110; 88%). A rate of 14.6% for complications and 3.3% for mortality are expected for these patients. In this study, most patients submitted for their first time to elective heart surgeries presented low risk to develop post-surgery complications and mortality.